Assessment of benz(a)pyrene pollution in Ufa River using time series analysis - Malkova Maria; Vozhdaeva Margarita; Serebryakov Pavel; Kantor Olga; Kantor Evgeny (E3S Web of Conferences)
The article analyzes the level of pollution of the Ufa River by benz(a)pyrene (B(a)P) for the period 1995-2023. The main sources of pollution are enterprises of fuel and energy and metallurgical complexes, motor transport and housing and communal services. Analysis of time series of B(a)P concentrations, carried out by means of decomposition into trend-cyclic, seasonal and random components, showed the dominance of the random component (83-97%). Comparison of long- term average B(a)P concentrations revealed a decrease between 2004 and 2012 and a slight increase between 2013 and 2023 compared to 1995-2003, with all values remaining below the MAC. Despite a slight increase in recent years, the overall trend for the entire period 1995-2023 indicates a decrease in B(a)P levels in the Ufa River, which is attributed to the implementation of environmental protection measures, in particular, the construction of new roads that reduce the traffic load in residential areas.